Dynamic behavior of a direct expansion evaporator under frosting condition. Part II. Field investigation on a shipping container - TSO, C; CHENG, Y; LAI, A (2006)
A field investigation is performed on the frost formation at an evaporator of a commercial full-scale refrigerated container that uses R-12 as the working refrigerant. Results when compared with those from a numerical model presented earlier show that the model is capable of predicting the dynamic behavior of a direct expansion evaporator under both non-frosting and frosting conditions. The air outlet and energy transferred compare well between experiment and model, and within 20% for the air pressure drop. The frost occurrence and propagation agree well generally, with the frost formation first occurring at the first row where the refrigerant enters the evaporator. (c) 2005 Elsevier Ltd and IIR. All rights reserved.